2019
DOI: 10.1177/2047487318825174
|View full text |Cite
|
Sign up to set email alerts
|

Exercise stress test in apparently healthy individuals − where to place the finish line? The Ferrari corporate wellness programme experience

Abstract: Aims The aim of our study was to assess the clinical significance of the exercise stress testing endpoints, namely 85% of maximal theoretical heart rate (MTHR), metabolic equivalent of task, and rating of perceived exertion (RPE), and their relation to electrocardiographic (ECG) changes in a healthy adult population. Methods A cross-sectional study was conducted on 408 males and 52 females (mean age 39.4 ± 8.6 years) who performed the maximal cycle ergometer exercise stress test until volitional exhaustion, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Unfortunately, this data is even more alarming, as subjects included in the sample of the present study were young adults, with a mean age of 29.18 years. This percentage is almost constant, and it is in line with data from previous studies [17,33], which highlight that a large portion of the population performs levels of PA below those recommended. Moreover, evidence suggests that regular PA among young people is declining [34] and being physical inactive during young adulthood can determine severe health effects later in life [35].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Unfortunately, this data is even more alarming, as subjects included in the sample of the present study were young adults, with a mean age of 29.18 years. This percentage is almost constant, and it is in line with data from previous studies [17,33], which highlight that a large portion of the population performs levels of PA below those recommended. Moreover, evidence suggests that regular PA among young people is declining [34] and being physical inactive during young adulthood can determine severe health effects later in life [35].…”
Section: Discussionsupporting
confidence: 90%
“…Indications and contraindications of PA have become a controversial discussion point among physicians and other health professionals [3,16]. Some research areas have contributed to defining risk factors related to PA and to implement algorithms and pre-participation screening strategies to avoid the harmful effects of PA in high-risk patients [17][18][19]. On the other hand, most national and international health organizations have proposed guidelines for PA, establishing the specific thresholds of type, duration, frequency and volume necessary to have positive effects on health [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not monitor BP continuously during the VO 2Max test, recorded posttest values should be considered normal, although higher than pre-test values (Table 2). Moreover, a previous study (Sirico et al, 2019) showed excessively higher BP-values during an exercise stress test among a small percentage of the general population.…”
Section: Discussionmentioning
confidence: 87%
“…The mean METs recorded on the whole sample was 1.66 (SD 0.22); it was 1.72 (0.18) in non-surgical group 1.58 (0.20) in surgical group (p=0.043) (Table 1). Due to the recognized impact of body weight on energy cost, 3 the correlation between BMI and recorded METs of the whole sample was investigated; there was a non-significant correlation (r=0.189, p=0.326) between these two variables in the present sample.…”
mentioning
confidence: 77%